Importance of bone marrow examination in cases of pancytopenia: A morphological study in a tertiary care center - Deepshikha Verma; Ranjan Yadav; Rajnikant Ahirwar; Pratibha Meena (Asian Journal of Medical Sciences, 2024)
Background: Anemia, leukopenia, and thrombocytopenia are all combined as pancytopenia. It could be a symptom of many diseases that directly or indirectly impact the bone marrow. The cause of pancytopenia, however, differs depending on the location. An essential step in determining the cause of pancytopenia is bone marrow aspiration (BMA). Aims and Objectives: This study aimed to determine the causes of pancytopenia and the morphology of the bone marrow in pancytopenia patients. Materials and Methods: This study was carried out over a year in the pathology department of a tertiary care facility in central India. Patients taking chemotherapy or radiation therapy were excluded from the study. Inclusion Criteria: Cases with hemoglobin <10 g/dL, total leukocyte count <4000/mm3, and platelet count <100,000/mm3 were included in this study. The patient’s posterior iliac crest was used for BMA. The Leishman stain was used to color BMA smears for microscopy. Results: This study comprised 51 cases of pancytopenia, with acute leukemia and megaloblastic anemia accounting for the majority (11 cases each out of 51), followed by dimorphic anemia (10/51), hypocellular marrow (9/51). The clinical symptom of generalized weakness and pallor was present in all instances (100%) and was followed by fatiguability (72%) and dyspnea (48%). The last two least frequent symptoms, lymphadenopathy, and hepatomegaly, were also present in many patients. A significant proportion of pancytopenia individuals experienced lymphadenopathy and hepatomegaly, which were the last two least prevalent appearances. Conclusion: In most cases, bone marrow aspiration in pancytopenia patients aids in determining the underlying reason. Understanding the illness process, planning future research, and managing cytopenia patients can all benefit from it.